2011
DOI: 10.1073/pnas.1102608108
|View full text |Cite
|
Sign up to set email alerts
|

In situ molecular NMR picture of bioavailable calcium stabilized as amorphous CaCO3biomineral in crayfish gastroliths

Abstract: Bioavailable calcium is maintained by some crustaceans, in particular freshwater crayfish, by stabilizing amorphous calcium carbonate (ACC) within reservoir organs—gastroliths, readily providing the Ca 2+ needed to build a new exoskeleton. Despite the key scientific and biomedical importance of the in situ molecular-level picture of biogenic ACC and its stabilization in a bioavailable form, its description has eluded efforts to date. Herein, using multinuclear NMR, we accomplish in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(137 citation statements)
references
References 58 publications
9
120
0
5
Order By: Relevance
“…This confirms the presence of ACC domains in both samples, as already proposed in sea urchin spines. 47 The FWHM of the ACC 13 C resonance from sea urchin skeletal elements is twice smaller than the one reported for synthetic ACC 58,59 and biogenic ACC gastrolith (enriched in P) 60,61 , suggesting that ACC in mature sea urchin large spines and test plates is more ordered than stable biogenic ACC in crayfish 60 and lobster 61 gastrolith. The relatively low organics content determined by TGA (about 1.4 wt.…”
Section: Crystallization Of Accmentioning
confidence: 71%
See 1 more Smart Citation
“…This confirms the presence of ACC domains in both samples, as already proposed in sea urchin spines. 47 The FWHM of the ACC 13 C resonance from sea urchin skeletal elements is twice smaller than the one reported for synthetic ACC 58,59 and biogenic ACC gastrolith (enriched in P) 60,61 , suggesting that ACC in mature sea urchin large spines and test plates is more ordered than stable biogenic ACC in crayfish 60 and lobster 61 gastrolith. The relatively low organics content determined by TGA (about 1.4 wt.…”
Section: Crystallization Of Accmentioning
confidence: 71%
“…Compared to synthetic ACC and other long-living biogenic ACC (gastrolith), 58,60 we showed that ACC in sea urchins is less disordered and that the low water content is most likely bound to the ACC phase (Ca:H 2 O 1:0.1). Therefore, the ACC in sea urchin skeletal elements is relatively anhydrous in comparison with other long-living biogenic ACCs (e.g.…”
Section: Acc and Intra-crystalline Organicsmentioning
confidence: 99%
“…Both calcium and bicarbonate are at least partially supplied from ambient water, although some organisms may internally store CaCO 3 to be used when needed (Horne et al, 2009;Akiva-Tal et al, 2011;Marin et al, 2012). Low concentrations of dissolved calcium can impose limits on CaCO 3 mineralization, so dissolved calcium and correlated parameters are used in biological models.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylated proteins have been characterized and hypothesized as playing a role in Cherax gastrolith ACC stabilization Glazer and Sagi, 2012;Glazer et al, 2010;Shechter et al, 2008b). Small phosphorylated metabolites of the glycolytic pathway have also been evidenced by Nuclear Magnetic Resonance (NMR) and thought to play an interacting role between matrix proteins and calcium ions forming complexes preventing the crystallization of CaCO 3 (Akiva-Tal et al, 2011;Sato et al, 2011).…”
Section: The Presence Of Phosphorus In Gastrolith Is Known Since the mentioning
confidence: 99%
“…Akiva-Tal et al, 2011;Bentov et al, 2010;Habraken et al, 2015;Luquet et al, 2016;Reeder et al, 2013;Reid et al, 2012;Sato et al, 2011). Nevertheless, it is well known that if the main mineral used by invertebrates for hardening their skeleton is calcium carbonate, numerous other minerals are also found, notably phosphate and silica-based minerals Knoll, 2003;Lowenstam, 1972;Lowenstam and Weiner, 1989;Murdock and Donohue, 2011;Simkiss and Wilbur, 1989).…”
mentioning
confidence: 99%